Onychomycosis with Green Nail Discoloration in an Immunocompromised Patient: A Case Report - Mulianto, Nurrachmat; Oktaviani, Trya (Health and Medical Journal, 2025)
Candida onychomycosis is an infection of the nails of the hands or feet caused by Candida sp. Green nail discoloration (GND) is a greenish discoloration of the nail due to bacterial infection, fungal infection or polymicrobial infection. Candida species fungi are fungal pathogens reported to be associated with GND. A 22-year-old female complained of greenish-yellow colored right thumb nail since 3 months ago. The patient has a history of systemic lupus erythematosus (SLE) since 1 year ago. Dermatological status examination of the digiti I manus dexter region showed onychodystrophy, subungual hyperkeratosis and greenish yellow discoloration of the nail plate. Based on the results of history, physical examination and supporting examination, the patient was diagnosed onychomycosis with GND. The diagnosis of onychomycosis can be established by history taking, physical examination and supporting examination in the form of dermoscopy, microscopic nail scraping with 20% KOH, fungal culture and nail biopsy with Periodic Acid-Schiff's (PAS) histochemical painting. Green nail discoloration is one of the clinical manifestations in cases of onychomycosis. Candida sp. is reported as one of the fungal pathogens associated with GND. Management of onychomycosis requires a long time and aims to eliminate fungal pathogens and improve nail condition.